2010
DOI: 10.1590/s1806-83242010000100005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of alternative methods for the disinfection of toothbrushes

Abstract: The aim of this study was to evaluate alternative methods for the disinfection of toothbrushes considering that most of the previously proposed methods are expensive and cannot be easily implemented. Two-hundred toothbrushes with standardized dimensions and bristles were included in the study. The toothbrushes were divided into 20 experimental groups (n = 10), according to microorganism considered and chemical agent used. The toothbrushes were contaminated in vitro by standardized suspensions of Streptococcus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 14 publications
3
55
0
10
Order By: Relevance
“…This result was supported by Salvia et al [46] and they remarked that this agent was as effective as 1% NaOCl and 2% chlorhexidine digluconate against Candida albicans , Escherichia coli, and Streptococcus mutans. On the contrary, Komiyama et al [63] investigated the effectiveness of 50% white vinegar for toothbrush disinfection and it was found to be effective for Staphylococcus aureus , Streptococcus mutans, and Streptococcus pyogenes, but not for Candida albicans . In this study, white vinegar was used in 50% and 100% concentrations for 10 min.…”
Section: Discussionmentioning
confidence: 99%
“…This result was supported by Salvia et al [46] and they remarked that this agent was as effective as 1% NaOCl and 2% chlorhexidine digluconate against Candida albicans , Escherichia coli, and Streptococcus mutans. On the contrary, Komiyama et al [63] investigated the effectiveness of 50% white vinegar for toothbrush disinfection and it was found to be effective for Staphylococcus aureus , Streptococcus mutans, and Streptococcus pyogenes, but not for Candida albicans . In this study, white vinegar was used in 50% and 100% concentrations for 10 min.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested different methods for disinfecting toothbrushes to prevent disease, 9,10 including the use of chemical agents, ultraviolet sanitizers, microwave irradiation, and dishwashing. 2,5,7,9,10,11,12 A lt houg h t h e d i si n fe c t ion me t ho d s of toothbrushes 1,2,9,12 have been investigated in several studies, to the best of our knowledge, no published study has reported the knowledge and behavior of dentists about toothbrush disinfection. Therefore, this study aimed to evaluate these aspects among dentists employed at a dental school in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, this study also show the effectiveness of CHX in a spray form 16,[20][21][22][23][24]35 . Nevertheless, CHX is an antiseptic agent which effectively killed bacteria by penetrating into cell cytoplasm and lyse cell component 36 . Previous report showed that bacteria might developed a resistant mechanism, if used for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…Previous report showed that bacteria might developed a resistant mechanism, if used for a long time. Most researchers are trying to use herbal extraction as an alternative 36,37 . The mechanism by which essential oils inhibits biofilm formation is unknown.…”
Section: Discussionmentioning
confidence: 99%